Estudo genômico da microbiota intestinal: a Influência dos probióticos e estilo de vida saudável na saúde metabólica de indivíduos com obesidade - Florêncio, Glauber Pimentel (2023)
Obesity is a complex metabolic disorder that has become a global epidemic with significant implications for public health. Studies have shown an association between dysbiosis of the gut microbiota and the development of obesity. One way to address dysbiosis is through changes in daily lifestyle habits. In addition to adopting positive lifestyle adjustments, there is a growing body of evidence that probiotics improve, maintain, or restore the gut microbiota, thereby opening the door to innovative strategies aimed at microbiota architecture and diversity. The objective of this research was investigate whether the treatment with probiotics, in conjunction with the adoption of healthy lifestyle habits, can influence the composition of the intestinal microbiota and contribute to the metabolic health of individuals with obesity. A prospective study was conducted with 45 obese adults. Participants received guidance on healthy lifestyle habits, were administered a probiotic supplement containing various microbial strains, and were monitored for 60 days. Clinical parameters, body composition, biochemical analysis, and assessment of the gut microbiota were conducted before and after the treatment. After a 60-day period, it was observed that the bacterial strains from the probiotic had become integrated into the patients' gut microbiota. Furthermore, participants demonstrated improvements in the regularity of physical activity, sleep quality, and more effective anxiety control. Positive changes in dietary habits were also noted, including a reduction in the consumption of processed products and a noticeable increase in water intake. There were reductions in body mass index, fasting glucose levels, insulin, HOMA-IR, LDL cholesterol, and triglycerides. Conversely, there was an increase in HDL cholesterol levels, along with improvements in bowel movement regularity and stool consistency. Evaluation of the gut microbiota indicated an elevation in microbial diversity, as well as a more balanced harmony between the Firmicutes and Bacteroidetes bacterial phyla. Changes in gut microbiota composition, dietary habits, increased physical activity, reduced anxiety, and improved sleep quality played a significant role in weight loss and the optimization of physiological and biochemical parameters in obese individuals.